The Ethics of Islamic Religious Education Teachers According to KH. Hasyim Asy`ari and Their Relevance to Improving the Quality of Islamic Education in Indonesia - Kiki Hibatulloh (LECTURES: Journal of Islamic and Education Studies, 2022)
The purpose of this research is to find out the views of KH. M. Hasyim Asy'ari about the ethics of Islamic religious education teachers and their relevance to improving the quality of Islamic education in Indonesia. This study uses a qualitative approach which is library research with descriptive methods. This study concludes that teachers should be careful in maintaining their attitudes, ethics and behavior in carrying out teaching and learning activities, and base each teaching behavior with the ethical values ​​of learning. In order for the quality of Islamic education in Indonesia to increase, teachers must have ethics; teacher ethics towards oneself, teacher ethics in the teaching and learning process, teacher ethics towards students, and ethics towards books (textbooks) as a tool for learning. For now it is felt very important to be appreciated again in the midst of a state of the education system that has been trapped in a material-oriented view. In the view of KH. M. Hasyim Asy`ari that material is not the goal of education. In this case KH. M. Hasyim Asy`ari places more emphasis on teacher ethics that a teacher must have a clean heart in teaching, asceticism, and a sincere intention to seek the pleasure of Allah. And must maintain the authority of the teacher towards students.